Production of sustainable fuel from food wastewater - Marziana, Mohamad (2010)
Nowadays, people are using more and more nonrenewable resources for energy. The world's supply of nonrenewable such as fossil fuels may run out. Other sources must be found to at least partly replace fossil fuels. Hydrogen fuel is seen as a constantly renewable source of energy as well. There are many ways or methods to produce hydrogen. Electrolysis is one of the simplest and easiest way to produce hydrogen. Usually we used blank water to produce hydrogen and oxygen from the electrolysis process. However, from this research the blank water is replaced with food wastewater that was collected from a cafeteria's discharge. The voltage for electrolysis process is fixed to 1011. The ampere is recorded every time the hydrogen is collected. The hydrogen is collected 5 times in 2 hours. The first electrolysis is added with 0.3 molar of catalyst and then the electrolysis is repeated using 0.5 molar of catalyst. The different molar of catalyst is used to determine which molar can produce more hydrogen. The electrolysis process is repeated to characterize the food wastewater in term of COD and BOD. Same with the first electrolysis, 0.3 molar and 0.5 molar of catalyst also added to the wastewater. The electrolysis process is running for two hours. Every 0, 10, 15, 30, 45, 60, 75, 90, 105 and 120 minutes, the sample is taken to characterize for BOD and COD. The raw wastewater which is the wastewater that not undergo the electrolysis process also is characterized in term of BOD and COD. The result of COD and BOD before and after electrolysis is compared.